1996
DOI: 10.1007/s004360050092
|View full text |Cite
|
Sign up to set email alerts
|

Alteration to one of three adenosine transporters is associated with resistance to Cymelarsan in Trypanosoma evansi

Abstract: Continuous exposure of Trypanosoma evansi bloodstream forms to Cymelarsan in vitro resulted in the induction of resistance to the drug over a period of 4.5 months. Induction of resistance to Cymelarsan was accompanied by increased resistance to both Arsobal and Berenil, but Cymelarsan-resistant trypanosomes remained sensitive to Suramin and Antrycide. Since resistance to arsenical drugs in trypanosomes has been linked to changes in adenosine uptake, the adenosine metabolism in drug-sensitive and drug-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Since Carter and Fairlamb showed that adenosine and adenine protect T. b. brucei from melarsen-induced lysis in vitro (6), several studies have pointed to a role for the P2 transport activity in the resistance of African trypanosomes to both melaminophenyl arsenicals and diamidines (2,5,27,29,30). A T. b. brucei gene, TbAT1, was found to encode an adenine-sensitive adenosine transporter when expressed in yeast (19), but formal proof that TbAT1 encodes the P2 activity in trypanosomes has awaited the gene deletion study presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Since Carter and Fairlamb showed that adenosine and adenine protect T. b. brucei from melarsen-induced lysis in vitro (6), several studies have pointed to a role for the P2 transport activity in the resistance of African trypanosomes to both melaminophenyl arsenicals and diamidines (2,5,27,29,30). A T. b. brucei gene, TbAT1, was found to encode an adenine-sensitive adenosine transporter when expressed in yeast (19), but formal proof that TbAT1 encodes the P2 activity in trypanosomes has awaited the gene deletion study presented here.…”
Section: Discussionmentioning
confidence: 99%
“…Nucleoside transport has been extensively studied in the trypanosomatidae, particularly in T. b. brucei and L. donovani , but to a much lesser extent also in Trypanosoma evansi [54–56], Trypanosoma equiperdum [57], Trypanosoma congolense [58], Trypanosoma vivax [59] and Trypanosoma cruzi [10].…”
Section: Purine Transport Activities In Various Protozoan Speciesmentioning
confidence: 99%
“…However, all drugs currently registered for use carry significant problems related to administration, toxicity, increasing incidence of treatment failure, and in the case of animal trypanosomiasis, drug resistance (1). Previous work has shown that defects in the P2 aminopurine transporter, encoded by the TbAT1 gene (the same gene in Trypanosoma equiperdum is referred to as TeAT1 [Trypanosoma equiperdum AT1] in this article), are linked to drug resistance in Trypanosoma brucei brucei (11,21), Trypanosoma brucei gambiense (22), and Trypanosoma brucei rhodesiense (28), as well as in Trypanosoma evansi (24,32) and T. equiperdum (3), very close phylogenetic relatives of T. brucei (27). The P2 transporter has been shown to be capable of carrying both melaminophenyl arsenical (11) and diamidine (10,14,15,18) classes of drug into African trypanosomes in the T. brucei group.…”
mentioning
confidence: 97%